Angular analysis of the decay B+ → K∗(892)+ μ + μ − in proton-proton collisions at √s = 8 TeV - CMS Collaboration; Damarseçkin, Serdal (Springer Science and Business Media Deutschland GmbH, 2021)
Angular distributions of the decay B+→ K∗(892)+μ+μ− are studied using events collected with the CMS detector in s = 8 TeV proton-proton collisions at the LHC, corresponding to an integrated luminosity of 20.0 fb−1. The forward-backward asymmetry of the muons and the longitudinal polarization of the K∗(892)+ meson are determined as a function of the square of the dimuon invariant mass. These are the first results from this exclusive decay mode and are in agreement with a standard model prediction.
Keywords: B physics; Hadron-Hadron scattering (experiments)